If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x(x+1)=2x+7
We move all terms to the left:
x(x+1)-(2x+7)=0
We multiply parentheses
x^2+x-(2x+7)=0
We get rid of parentheses
x^2+x-2x-7=0
We add all the numbers together, and all the variables
x^2-1x-7=0
a = 1; b = -1; c = -7;
Δ = b2-4ac
Δ = -12-4·1·(-7)
Δ = 29
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-\sqrt{29}}{2*1}=\frac{1-\sqrt{29}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+\sqrt{29}}{2*1}=\frac{1+\sqrt{29}}{2} $
| -404=t+(-719) | | 1/3a=10 | | 91=1+5x | | 2k-7=-23 | | -1x+2=-2x-1 | | 11t-11t+5t-2=13 | | 3/8x-1/3×+6=1/6x | | 1/2(2x+12)=1/4(8x-16) | | 3(2x+)=8x+21 | | -10(s+3)=-92 | | -2+11=3x-4 | | 4(3x+7)=-32+48 | | -8d=-144 | | 17s=-17 | | O=18+9(m-2) | | 12=2m+3+7 | | 3(x+6)+7x=-32 | | -4(g+8)=7+4g | | 2(3x+6)=-44+14 | | h+-267=332 | | 5(2n+6)=4(5n+5) | | 2a+3=126+4a | | 13+b=34 | | -10=x/6-3 | | -6h+-2h+-17=-1 | | 8x*5=9x-8 | | 0=18+9(m-2 | | n-(137)=492 | | -12z=-12 | | x/4+3=38 | | 25x+25=24x+20 | | -3=c/3-12 |